Maternal urinary bisphenols and phthalates in relation to estimated fetal weight across mid to late pregnancy. (April 2023) - Cowell, Whitney; Jacobson, Melanie H.; Long, Sara E.; Wang, Yuyan; Kahn, Linda G.; Ghassabian, Akhgar; Naidu, Mrudula; Torshizi, Ghazaleh Doostparast; Afanasyeva, Yelena; Liu, Mengling; Mehta-Lee, Shilpi S.; Brubaker, Sara G.; et al.
Highlights: Bisphenols and phthalate metabolites may be associated with altered fetal growth. Associations were greatest among small and large fetuses and varied by sex. Associations were strongest for replacement DEHP phthalates (DiNP and DnOP). Effects of exposure on fetal growth may occur by the second trimester. Abstract: Background: Bisphenols and phthalates are high production volume chemicals used as additives in a variety of plastic consumer products leading to near ubiquitous human exposure. These chemicals have established endocrine disrupting properties and have been linked to a range of adverse reproductive and developmental outcomes. Here, we investigated exposure in relation to fetal growth. Methods: Participants included 855 mother-fetal pairs enrolled in the population-based New York University Children's Health and Environment Study (NYU CHES). Bisphenols and phthalates were measured in maternal urine collected repeatedly during pregnancy. Analyses included 15 phthalate metabolites and 2 bisphenols that were detected in 50 % of participants or more. Fetal biometry data were extracted from electronic ultrasonography records and estimated fetal weight (EFW) was predicted for all fetuses at 20, 30, and 36 weeks gestation. We used quantile regression adjusted for covariates to model exposure-outcome relations across percentiles of fetal weight at each gestational timepoint. We examined sex differences using stratified models. Results: Few statistically significant associations were observed across chemicals, gestational time periods, percentiles, and sexes. However, within gestational timepoints, we found that among females, the molar sums of the phthalates DiNP and DnOP were generally associated with decreases in EFW among smaller babies and increases in EFW among larger babies. Among males, the opposite trend was observed. However, confidence intervals were generally wide at the tails of the distribution. Conclusion: In this sample, exposure to bisphenols and phthalates was associated with small sex-specific shifts in fetal growth; however, few associations were observed at the median of fetal weight and confidence intervals in the tails were wide. Findings were strongest for DiNP and DnOP, which are increasingly used as replacements for DEHP, supporting the need for future research on these contaminants.